Effect of connection transverse reinforcement on the behavior of GFRP-RC T-connections: Numerical investigation. (11th January 2023) - Safdar, Muhammad; Sheikh, M. Neaz; Hadi, Muhammad N.S.
Highlights: Numerical approach developed to predict the cyclic behavior of GFRP-RC connections. Numerical model showed good correlations between load-drift ratio with test results. Numerical study to investigate transverse reinforcement on GFRP-RC connections. Abstract: This study numerically investigates the cyclic behavior of glass fiber-reinforced polymer (GFRP) reinforced concrete exterior beam-column (T-BC) connections (GFRP-RC T-BC connections) with varying amounts of transverse reinforcement (TR) in the connection panel. The amount of TR required to provide adequate confinement and shear strength to the GFRP-RC T-BC connections has not yet been fully understood. The primary objective of this study was to evaluate the effects of TR configuration and amount of TR on the load-drift ratio response, strain distributions and shear strength of the GFRP-RC T-BC connections. The numerical investigation was conducted using the numerical models developed in ATENA software and validated against the test results of four T-BC connections (one steel-RC and three GFRP-RC). The TR ratio and TR configurations (2 leg, 3 leg, and 4 leg horizontal stirrups) in the connection panel were the main parameters of the numerical study. Results of the numerical study indicated that increasing the TR ratio in the connection panel to 0.72% significantly enhanced the peak load, stiffness and drift ratio capacity of the GFRP-RC T-BC connection. Four leg TR configuration showed significantly better performance of the GFRP-RC T-BC connections due to the higher confinement factor than the other TR configurations. A shear strength equation was proposed for the GFRP-RC T-BC connections, which represents a linear relationship between shear strength and the TR ratio up to 0.60%, followed by stable shear strength of 0.85 f c ′ for a TR ratio up to 1.30%.